IMPLEMENTASI KEBIJAKAN PROGRAM KEBERSIHAN, KEINDAHAN DAN KETERTIBAN (K3) UNTUK MENINGKATKAN KESADARAN MASYARAKAT TERHADAP PENCEGAHAN PENCEMARAN LINGKUNGAN HIDUP - Rustam Dirgantara Putra Suharto; Yaqub Cikusin; Hayat (Halu Oleo University, 2023)
The purpose of this study is to determine the factors that influence the implementation of hygiene, beauty and order (K3) program policies to increase public awareness of preventing environmental pollution. The author used a descriptive qualitative method, using a qualitative approach. Where researchers use sources of information in the field to find information as deeply as possible. With this approach, the author can describe the conditions and situations in the field based on the data sources obtained both through observation techniques, interviews and documentation. The research informants in this study were officers of the Environmental Service (DLH) and the Civil Service Police Unit (Satpol PP) of West Sumba Regency. The place of this study is located in Wailiang Village, West Sumba Regency. The results showed that the Implementation of the Cleanliness, Beauty and Order (K3) Program Policy to Increase Public Awareness of Environmental Pollution Prevention has been implemented properly. However, some obstacles are still encountered from several parties, both from the government, officials and the community. The need for cooperation between the government, officials and local residents to build a clean and orderly city environment, so that the image of a city is well known in wide circles and is able to increase the economic market in the are.